Penerapan Pola Hidup Bersih dan Sehat Melalui Metode Penyuluhan Pentingnya Mandi bersih dan Benar pada Anak Usia Dini di Tk Wadi Fatimah - Sofiyati Sofiyati; Cinta Arifah; Seftiyani Seftiyani; Angella Nur; Sekar Tri; Syifa Salsabila; Nursofiyanti Nursofiyanti; Salsabilla Nur (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Clean and healthy living behavior (PHBS) is a crucial strategy for enhancing health status, as many diseases can be prevented by adopting healthy lifestyle habits. School-aged children are particularly vulnerable to health issues because they spend a significant amount of time outside the home and away from parental supervision. This counseling activity on clean and healthy living behaviors aimed to educate children at Wadi Fatimah Kindergarten, helping them to practice daily habits such as maintaining personal hygiene (including proper bathing techniques). The activity utilized a counseling method, supported by tools such as laptops, projectors, door prizes, PowerPoint presentations, and bathing props. A total of 76 children, aged 5-6 years, participated in the program. The counseling session was successful, with the children showing great enthusiasm while watching educational videos on bathing and actively engaging in discussions. They demonstrated an understanding of the PHBS concept and knew how to apply it in their daily lives. The discussion results revealed that 80% of the children were capable of bathing themselves, while 20% were still assisted by their parents